2004
DOI: 10.1111/j.1468-0432.2004.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Trade Unions, Gender and Claims under Irish Employment Equality Legislation

Abstract: This article examines trade union activity in representing claimants at Equality Officer investigations under the Republic of Ireland's Employment Equality Act, 1977. This is set in the context of traditional trade union support for gender segregation in employment and the observation that trade union decision-making bodies still tend to be heavily male dominated. Use of the Act by trade unions is shown to have been mainly reactive rather than strategic. Evidence is presented that, while some individual union … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Programmes like W2T are often criticized for failing to orchestrate the practical effects and outcomes that they are enacting as their goals. Numerous gender equality programmes have been launched (Cunningham et al ., 1999; Duke, 1997; Philips, 2005; Quinn, 2004; Woodward and Winter, 2006) with no significant changes in equal opportunities. Rather than assuming that such programmes are poorly managed or incompetently designed, one should examine the very design and content of such programmes, paying specific attention to the contradictions inherent to multiple objectives: the multifaceted ambition of reflecting upon gendered inequalities, the establishment of a shared vocabulary to address such conditions and the promotion of solutions to perceived problems.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Programmes like W2T are often criticized for failing to orchestrate the practical effects and outcomes that they are enacting as their goals. Numerous gender equality programmes have been launched (Cunningham et al ., 1999; Duke, 1997; Philips, 2005; Quinn, 2004; Woodward and Winter, 2006) with no significant changes in equal opportunities. Rather than assuming that such programmes are poorly managed or incompetently designed, one should examine the very design and content of such programmes, paying specific attention to the contradictions inherent to multiple objectives: the multifaceted ambition of reflecting upon gendered inequalities, the establishment of a shared vocabulary to address such conditions and the promotion of solutions to perceived problems.…”
Section: Discussionmentioning
confidence: 96%
“…, 2004; Kossek et al ., 2005; Wajcman, 1998; SOU, 2003). More specifically, studies of organizations as diverse as trade unions (Quinn, 2004), a university (Duke, 1997), the British army (Woodward and Winter, 2006), the civil service (Cunningham et al ., 1999), a large utility company (Helms Mills, 2005) and a law firm (Philips, 2005) suggest that equal opportunity is hindered by a variety of institutionalized gendered beliefs and assumptions. The limited effect of such programmes is daunting for anyone who believes that the issue deserves more detailed analysis and is concerned with a working life that offers a more equal distribution of opportunity.…”
Section: Introductionmentioning
confidence: 99%
“…When reforming organizations that are inherently conservative and loosely coupled (Orton and Weick, ; Pfeffer and Salancik, ; Weick, ), i.e., designed to accommodate external pressures, change must derive from many sources and not just from the top or from individual, enterprising actors. Feminist scholars and gender theorists have demonstrated over the years that social reform and organization change only happen slowly and over time, and only after significant efforts have been made (Cunningham et al ., ; Helms Mills, ; Kantola, ; Martin, ; Philips, ; Quinn, ; Webb, ; Wilson et al ., ). While the autonomous and visionary agent of change is an appealing figure in storytelling, and deeply embedded in the managerialist folklore, it is still, in many cases, a deceiving image of agency in institutional fields, characterized by multiple responsibilities, long‐term traditions and organizational histories, and deep‐seated professional domains of jurisdiction.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of implementing gender‐related changes is a recurring theme in projects focused on the promotion of gender equality in organizations. Yet numerous studies have reported unsuccessful such projects (Crawford and Mills, ; Cunningham et al , ; Duke, ; Helms Mills, ; Phillips, ; Quinn, ; van den Brink and Benschop, , ; Woodward and Winter, ). A question then arises: can planned changes result in visible and sustainable change in the ways gender is constructed in organizations?…”
Section: Introductionmentioning
confidence: 99%